Growth Characteristics of Vibrio parahaemolyticus Isolated from Lobster (Panulirus sp.) Under Different Temperatures, pH, and NaCl Concentrations - Ansar, Novalina Maya Sari; Ijong, Frans Gruber; Tanod, Wendy Alexander; Cahyono, Eko; Pumpente, Obyn Imhart; Palawe, Jaka Frianto Putra (Bioma : Berkala Ilmiah Biologi, 2023)
Vibrio parahaemolyticus is a bacterium found in estuaries and marine and is a pathogenic bacterium that harms human health. Vibrio parahaemolyticus can contaminate fishery products and potentially contaminate lobster products in North Sulawesi. This study was conducted to determine the presence of V. parahaemolyticus in lobsters collected in two shelters in North Sulawesi. This study also serves as a monitoring function and a means of information on the presence of V. parahaemolyticus. The samples used were lobsters (Panulirus sp.) taken from Malalayang and Tuminting shelters in North Sulawesi. Observations in this study include total bacteria, total Vibrio, and identified V. parahaemolyticus. Isolates of V. parahaemolyticus were characterized by their growth at different temperatures (5, 37, 43 oC); pH (5 - 9); and concentrations of NaCl (0, 1, 3, 5%). The results show total plates for lobster meat from Malalayang 4.3×104 ‒ 1.0×105 CFU/g, while from Tuminting shelter 1.4×104 ‒ 3.9×104 CFU/g. The total plate on lobster gills from Malalayang is 6.2×104 ‒ 1.2×105 CFU/g, while from Tuminting shelter 2.0×104 ‒ 6.7×104 CFU/g. Total Vibrio in lobster meat from Malalayang 6.2×103 ‒ 1.4×104 CFU/g, while from Tuminting shelter 5.2×103 ‒ 7.9×103 CFU/g. Total Vibrio in lobster gills from Malalayang 8.5×103 ‒ 4.6×104 CFU/g, while from Tuminting shelter 7.8×103 ‒ 9.5×103 CFU/g. The Gram staining analysis obtained 96 isolate strains with Gram-negative rods, and 42 strains showed characteristics as V. parahaemolyticus based on the biochemical assay. Vibrio parahaemolyticus can grow optimally at 37°C, pH 7‒8, and NaCl concentration 3‒5%.